Acute malnutrition associated with mid-upper arm circumference among under-five children in tribal areas, India: a cross-sectional study - Shraboni Patra; Shashikant Sambharkar; Sheetal Harode; Kalpana Barde; Amita Pillewan (Public Health Nutrition)
Abstract